Tarjuma-yi Anājīl-i arbaʿa - Khātūnābādī, Mīr Muḥammad Bāqir, (Miras Maktoob, ISBN: 9789004365452., 2019)
Mīr Muḥammad Bāqir Khātūnābādī (d. 1127/1715) was a Shīʿī scholar who entertained close relations with the Safavi ruler Shāh Sulṭān Ḥusayn (d. 1139/1726-27) in Isfahan. In the late 17th century, Isfahan was the center of international commerce and diplomacy in Persia. Besides serving the commercial interests of their homeland, some of the foreign representations also had missionaries in their ranks, with the obvious purpose of propagating Christianity among the local population. To this end, they also distributed Arabic copies of the Gospels. In those days, Isfahan was the scene of Christian-Muslim dialogue and polemics. The Persian translation of the Gospels published in this volume was made by Khātūnābādī on the order of Shāh Sulṭān Ḥusayn. It was meant to provide Muslim scholars with the necessary background for their debates. It is a critical, documented, almost scholarly translation, with all the weak points of the Gospels recorded in its margins.